2004
DOI: 10.1260/026361704323150953
|View full text |Cite
|
Sign up to set email alerts
|

The Adsorption of Pentachlorophenol from Aqueous Solutions onto Exchanged Al-MCM-41 Materials

Abstract: ABSTRACT:The ability of a mesoporous molecular sieve to adsorb chlorinated phenols was studied experimentally. Thus, the adsorption isotherms of pentachlorophenol (PCP) from aqueous solutions were measured on (M)Al-MCM-41 (M = Na, Cr 3+ ) at intervals of 10 K between 303 K and 323 K. The experimental isotherms obtained were of the S-type in terms of the classification of Giles and co-workers. The best fit of the adsorption isotherm data was obtained using the Freundlich model. The adsorption affinity of PCP in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…A similar trend of change in DH for PCP adsorption on synthetic Al and Si compounds was observed with a negative DH average [35]. On the contrary, adsorption of 2,4-DCP, 2,4,6-TCP, and PCP on an allophanic soil increased with temperature, indicating an endothermic reaction, which was attributed to the formation of monodentate outer-and inner-sphere complexes between deprotonated organic molecules and active sites of the variable-charge soil [36].…”
Section: Effect Of Temperature On Tecp Adsorptionsupporting
confidence: 74%
“…A similar trend of change in DH for PCP adsorption on synthetic Al and Si compounds was observed with a negative DH average [35]. On the contrary, adsorption of 2,4-DCP, 2,4,6-TCP, and PCP on an allophanic soil increased with temperature, indicating an endothermic reaction, which was attributed to the formation of monodentate outer-and inner-sphere complexes between deprotonated organic molecules and active sites of the variable-charge soil [36].…”
Section: Effect Of Temperature On Tecp Adsorptionsupporting
confidence: 74%
“…Good agreement between the experimental isotherms and the Freundlich model was found in the case of systems: pentachlorophenol/(M)Al-MCM-41 [21], and toluene/activated carbon [22].…”
Section: Applied Model Non Linear Form Linear Formmentioning
confidence: 53%
“…This time was used for all the equilibrium adsorption experiments reported here. The results concerning the adsorption of PCP from aqueous solution by activated sludge biomass [29] and by (M)Al-MCM-41 [30] also showed that the equilibrium was attained within less than 2 h. Adsorption isotherms are depicted in Fig. 2 as plots of the amount adsorbed per g of adsorbent (mmol/g) (Q e ) as a function of the quantity of PCP remaining in the equilibrium solution (mmol/l) (C e ).…”
Section: Adsorption Isotherms Of Pcpmentioning
confidence: 91%
“…The fits of all the isotherms by the Freundlich model were insufficient to explain the data, in particular for D-900 and especially D-1000, although this model has been successfully applied to describe the sorption of PCP onto activated sludge biomass [29], peat/bentonite mixtures [40], (M)Al-MCM-41 [30], chitosan [10], and compost [11].…”
Section: Fitting the Models To The Experimental Datamentioning
confidence: 99%